Proceso de atención de enfermería en paciente con gangrena de fournier basada en la teoría de Marjorie Gordon - Cuenca Cuenca, Yajaira Marisol; Gorostiza Castro, María Juleysi (Machala : Universidad Técnica de Machala, 2022)
Introduction: Fournier's gangrene fasciitis is a generalized infection of the skin and soft tissues with massive destruction of various planes of the fascia, vascular compromise, and forms of necrotizing cellulite that condition microbial proliferation; It presents perianal location, often with a genitourinary focus compromising the scrotal region, without discrimination of sex or age. The associated pathologies and considered as the source of Fournier's gangrene are diabetes mellitus (66.6%); chronic smoking (47.6%); high blood pressure (42.8%); obesity (23.8%); chronic kidney disease (19.6%) and prostration (12.5) (3). In the present case study, the object of study has a personal history of high blood pressure, with a higher risk of contracting this disease. This pathology has an incidence of 1.6 cases per 100,000 men, with a high percentage between 50 and 60 years of age; on the other hand, women have a ratio of 10:1. Vargas and collaborators in their study highlight that this infectious pathology has a high mortality rate that varies between 20% and 43%. In Ecuador, according to data from the National Institute of Statistics and census in the year (2020), data provided from the year 2018, 92 patients with Fournier's gangrene (70 men and 22 women) were registered and in 2019 73 people were discharged (57 men and 16 women). The present investigation is based on the theory of Marjory Gordon, a theory focused on identifying the problems or alterations in the health of the patient through determining the altered patterns in the well-being of the patient in a patient diagnosed with Fournier's Gangrene.
Introducción: La Fascitis Gangrena de Fournier, es una infección generalizada de la piel y partes blandas con destrucción masiva de diversos planos de la fascia, compromiso vascular, y formas de celulitis necrotizantes que condicionan la proliferación microbiana; presenta localización perianal, a menudo de foco genitourinario comprometiendo la región escrotal, sin discriminación de sexo, ni edad. Las patologías asociadas y consideradas como foco de origen de la gangrena de Fournier esta la diabetes mellitus (66,6%); tabaquismo crónico (47,6%); hipertensión arterial (42,8%); obesidad (23,8%); enfermedad renal crónica (19,6%) y postración (12,5) (3). En el presente estudio de caso, el objeto de estudio presenta antecedentes personales de hipertensión arterial, siendo mayor el riesgo de contraer esta enfermedad. Esta patología, tiene incidencia de 1,6 casos por cada 100.000 hombres, con un alto porcentaje entre los 50 a 60 años de edad; por otro lado, las mujeres presentan una proporción de 10:1. Vargas y colaboradores en su estudio destacan que esta patología infecciosa tiene una tasa alta de mortalidad variable entre 20% al 43%. En Ecuador, según datos del Instituto Nacional de Estadísticas y Censo en el año (2020), datos proporcionados del año 2018 se registraron 92 pacientes con gangrena de Fournier (70 hombres y 22 mujeres) y en el 2019 egresaron 73 personas (57 hombres y 16 mujeres). La presente investigación está fundamentada en la teoría de Marjory Gordon, teoría focalizada en identificar los problemas o alteraciones en la salud del a través de determinar los patrones alterados en el bienestar del paciente en con diagnóstico de Gangrena de Fournier.
Keywords: PROCESO DE ATENCION DE ENFERMERIA; GANGRENA DE FOURNIER; MARJORY GORDON